ANALISIS BUDAYA WESTERNISASI TERHADAP KEBUDAYAAN NUSANTARA DI KALANGAN MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG - Ananda, Masykuria Luthfia; Jadidah, Ines Tasya; Sakinah, Anastasia Putri; Pebriani, Erin; Anggraini, Talita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research focuses on the responses of Madrasah Ibtidaiyah Teacher Education students at Raden Fatah State University, Palembang, to the westernization of Indonesian culture. The method used in this research is the Qualitative Method with a Descriptive approach. From the research that has been carried out, the results show that westernization can have a good impact, as western culture has encouraged advanced technological innovation, making it easier to carry out various jobs. However, there are also some of them who say that Westernization culture has quite a negative impact if it is not controlled properly, such as less polite speech or communication styles, depending on the context and how they adapt it to their own Indonesian culture. As for the factors that influence the existence of westernized culture, namely lack of sensitivity to science and technology, consumptive behavior towards information goods from abroad, the widespread development of western culture and acculturation (mixing) of cultures caused by the ever-increasing flow of globalization, lack of public awareness in sorting out good or bad culture. thus affecting daily activities in the developing surrounding environment.